2020
DOI: 10.3934/neuroscience.2020027
|View full text |Cite
|
Sign up to set email alerts
|

Gαq protein signaling in the bed nucleus of the stria terminalis regulate the lipopolysaccharide-induced despair-like behavior in mice

Abstract: Major depressive disorder (MDD) is highly comorbid with anxiety disorders. It has been reported that the bed nucleus of the stria terminalis (BNST) is important for the induction of anxiety and MDD. Recently, the Gαq protein signaling within the BNST is involved in the induction of anxiety through Gαq protein signaling-mediated RNA-editing of GluR2 subunit, which produces the calcium (Ca 2+ )-impermeable α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor. On the other h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…However, their immobility time during the second 5 min period of the TST was longer than that of the first 5 min. We have previously suggested that immobility time during the second 5 min period of the TST was longer due to the induction of learned despair [41,43]. The present results indicate that despair behavior was reduced in mice with a 2% NaCl intake for 5 consecutive days, but that learned despair was not affected.…”
Section: Discussionsupporting
confidence: 49%
See 3 more Smart Citations
“…However, their immobility time during the second 5 min period of the TST was longer than that of the first 5 min. We have previously suggested that immobility time during the second 5 min period of the TST was longer due to the induction of learned despair [41,43]. The present results indicate that despair behavior was reduced in mice with a 2% NaCl intake for 5 consecutive days, but that learned despair was not affected.…”
Section: Discussionsupporting
confidence: 49%
“…3C), indicating that the NaCl intake prevented the TMT-induced despair behavior. In our previous work, we demonstrated that the learned despair behavior could be observed in the last 5 min of 10-min TST in subsequent of the first 5 min [41,43]. Therefore, we investigated whether the NaCl intake affected the induction of learned despair behavior.…”
Section: Effect Of 2% Nacl Intake On the Immobility Time During Tst A...mentioning
confidence: 95%
See 2 more Smart Citations
“…However, anatomical studies indicate that the vast majority of BNST input to the parvocellular PVN is GABAergic [ 88 ], suggesting that the BNST provides largely inhibitory modulatory input to the HPA axis [ 89 ]. Moreover, Fukuwada et al [ 90 ] recently presented evidence for a role of the BNST in regulating endotoxin-induced despair-like behaviour in mice via Gαq protein signalling. Finally, the BNST is involved in control of inflammation-associated loss of appetite [ 91 ].…”
Section: Discussionmentioning
confidence: 99%